THE PREVALENCE OF UNWANTED SEXUAL EXPERIENCES AMONG BELGIAN AND SOUTH AFRICAN STUDENTS - Revell, Arlynn Tracy; Vansteenwegen, Alfons; Nicholas, Lionel John (Social Work/Maatskaplike Werk, 2007)
Child sexual abuse (CSA) is a global problem and South Africa has been identified as a high-CSA incidence country (Jewkes, 2002; Meier, 2002; New York Times, 2002 cited in Women’s International Network, 2002). Belgium is a low-CSA incidence country (Finkelhor, 1994) and the comparison of two similar populations from these countries would elucidate differences in unwanted sexual experiences of these two settings, reflecting social and cultural variables that may affect the problem. Back, Jackson, Fitzgerald, Shaffer, Salstrom and Osman (2003), contend that very few studies have compared individuals of different nationalities and also those residing in their own countries, which limits the understanding of potential cultural differences regarding CSA. In their study of 65 North American and 88 Singaporean women college students they found 15,4% of North American respondents had been exposed to CSA compared to 4,5% of Singaporean respondents, the majority of whom did not consider themselves as being abused. Miller, Johnson and Johnson (1991) contend that self-report biases and definitional problems permeate CSA research and they developed an Early Sexual Experience Checklist (ESEC) which seeks to avoid such problems. They argued that, because the ESEC assesses an explicit variety of non-coital responses and provides a non-restrictive response format, a high incidence of unwanted sexual experiences may be reported as is the case in their study.